Ethanol From Olive Paste During Malaxation, Exploratory Experiments. Issue 1 (23rd November 2018) - Masella, Piernicola; Guerrini, Lorenzo; Angeloni, Giulia; Zanoni, Bruno; Parenti, Alessandro
Abstract : Ethanol is a precursor of ethyl esters in olive oil. Its presence is generally ascribed to microbial degradation of damaged olives. At the same time, it is an anaerobic metabolite that naturally accumulates in olive fruit during ripening. As the possible link with olive processing is poorly studied, this laboratory‐scale experiment measures gaseous ethanol in the headspace above olive paste malaxated in sealed conditions. Malaxation take place in the presence or absence of oxygen, using sanitized or untreated olives. The findings show that ethanol accumulates in the headspace in oxygenated trials, reaching roughly 80 μmol kg −1 of olive paste. Under anoxic conditions ethanol accumulation is ten times higher, while olive treatment is not significant. Ethanol kinetics during malaxation are modeled as a biexponential system in which two components are simultaneously present, originating from parallel reactions at different constant rates. The first is the ethanol present in the olives and gradually released in the headspace. The second is ethanol neoformation under anoxic conditions. Under oxygenated conditions, the first component predominates, while under anoxic conditions, the opposite holds. Practical Application : Online monitoring of gaseous ethanol above olive paste during malaxation could easily be implemented in olive oil processing plants. Ethanol kinetics could indicate the presence of unwanted anoxic conditions and help in setting appropriate oxygen levels in the kneaded paste. Future studies may find a link between ethanol kinetics in the malaxation headspace, and the occurrence of ethyl esters in oils. If this is the case, operators would be able to fine‐tune the process to avoid unwanted effects. Ethanol is an anaerobic metabolite that naturally accumulates in olive fruit during ripening. Gaseous ethanol is found to be released from the olive paste during malaxation (sealed conditions). Furthermore, under anoxicity, the ethanol release is roughly ten times higher in response to the absence of oxygen, that is, cell anaerobic respiration take place. Abstract : Ethanol is an anaerobic metabolite that naturally accumulates in olive fruit during ripening. Gaseous ethanol is found to be released from the olive paste during malaxation (sealed conditions). Furthermore, under anoxicity, the ethanol release is roughly ten times higher in response to the absence of oxygen, that is, cell anaerobic respiration take place.